Enhancing The Skill In Stating Research Questions Using A Contextualized Module - Villonez, Glen L. (Shanti Journal, 2022)
This classroom based action research delved on enhancing the skill in stating a research question in Practical Research 1 subject of Late Afternoon Senior High School students. The study utilized an action research design. This was conducted in Francisco Bangoy National High School during the second semester of school year 2017-2018. Two students were taken into consideration as participants of the study. Baseline data were gathered to assess their performance. Contextualize module was utilized as the tool in helping students master the competency. Also, interview was conducted to validate the results of the quantitative findings. Data were analyzed using Thematic Content Analysis. The findings revealed that students performance after the intervention was implemented has recorded significant increased. Similarly, students claimed that the intervention was helpful and effective in addressing their need. Further, from those meaningful results, it can be reflected that students’ success in the class was largely attributed to the kind of intervention implemented by the teacher which was suited to their need. Undeniably, the use of a module has helped them master the required learning competency. Hence, use of a module may be offered to teachers handling research subject.